Functional outcomes of reverse distal femoral locking plate in the extra capsular fractures of proximal femur - Singh, Jaspreet; Selhi, Harpal Singh; Gupta, Rahul; Kaur, Gurleen (International Journal of Research in Orthopaedics, 2019)
Background: The optimal management of unstable proximal femoral fractures is controversial. In this prospective study, the functional outcomes of reverse distal femoral locking plate for the treatment of comminuted unstable proximal femoral fractures were assessed. Objectives were to study the functional outcomes of reverse locking plate in extra-capsular fractures of the proximal femur, with respect to quality of reduction, time to bony union, mobility achieved, complications of the procedure, secondary procedures performed (if any) and delayed complications like implant breakage, delayed union, non-union. Methods: 17 patients with unstable proximal femoral fractures were assessed and managed with reverse distal femur plates, and evaluated with X-ray, physical examination, Palmer and Parker mobility score. Results: Union was achieved in all the patients, with average time to union 6.43±1.18 months (range 3-12 months). There was one loosening of implant and wound breakdown, which was managed conservatively. One case of loosening of proximal screws was there, but the fracture united in 9 months with some varus angulation. Superficial infection occurred in one patient, which healed after debridement and IV antibiotics. Conclusions: Taking into consideration the simple surgical technique, good healing rate and minimum complications, it is strongly recommended to use reverse locked distal femoral plates for the management of proximal femoral fractures and further in lean patients, sum-muscular MIPPO should be attempted.